Bioinformatics-based analysis reveals elevated CYTL1 as a potential therapeutic target for BRAF-mutated melanoma - Tao, Lei; Cui, Yingyue; Sun, Jiarui; Cao, Yu; Dai, Zhen; Ge, Xiaoming; Zhang, Ling; Ma, Run; Liu, Yunyao (Frontiers in Cell and Developmental Biology, 2023)
Despite many recent emerging therapeutic modalities that have prolonged the survival of melanoma patients, the prognosis of melanoma remains discouraging, and further understanding of the mechanisms underlying melanoma progression is needed.Melanoma patients often have multiple genetic mutations, with BRAF mutations being the most common. In this study, 24 overlapping genes were identified by analyzing the TCGA database, GEO database, and other databases for differentially expressed genes (DEGs) common to melanoma and normal tissue, BRAF-mutated melanoma, and BRAF wild-type melanoma. Among them, CYTL1 was highly expressed in melanoma, especially in BRAF-mutated melanoma, and the high expression of CYTL1 was associated with epithelial-mesenchymal transition (EMT), cell cycle, and cellular response to UV. In melanoma patients, especially BRAF-mutated melanoma patients, clinical studies showed a positive correlation between increased CYTL1 expression and shorter overall survival (OS) and disease-free survival (DFS). In vitro experiments further confirmed that the knockdown of CYTL1 significantly inhibited the migration and invasive ability of melanoma cells. In conclusion, CYTL1 is a useful prognostic biomarker and a potentially effective therapeutic target in melanoma.